2010
DOI: 10.1002/ejic.201000374
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Ultra‐Small Manganese Oxide Surface Doped Gadolinium Oxide (Gd2O3@MnO) Nanoparticles for MRI Contrast Agent

Abstract: We have developed ultra‐small gadolinium oxide (Gd2O3) nanoparticles, which are surface‐doped with manganese oxide (MnO) (abbreviated as Gd2O3@MnO). The surface‐doped nanoparticles ranged from 1 to 2 nm in diameter. They were further coated with hydrophilic biocompatible lactobionic acid. In‐vitro tests of the sample solution indicated clear dose‐dependent contrast enhancements in both T1 and T2 map images, showing that the nanoparticles may be used as both T1 and T2 MRI contrast agents. Their performance as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Choi et al developed surface-doped with manganese oxide (MnO) Gd-NPs abbreviated as Gd-NPs@MnO ranging from 1 to 2 nm in diameter, coated with hydrophilic biocompatible compound, lactobionic acid (LA). In-vitro studies revealed dose-dependent contrast enhancements in both T 1 and T 2 map images, establishing their potential as both T 1 and T 2 MRI CAs [151]. Mixed Zn(II)/Gd(III) oxide NPs with approximately 8 mole% of Zn with an average diameter of 2.1 nm were synthesized by Tegafaw et al in their studies.…”
Section: Organic and Inorganic Moleculesmentioning
confidence: 97%
“…Choi et al developed surface-doped with manganese oxide (MnO) Gd-NPs abbreviated as Gd-NPs@MnO ranging from 1 to 2 nm in diameter, coated with hydrophilic biocompatible compound, lactobionic acid (LA). In-vitro studies revealed dose-dependent contrast enhancements in both T 1 and T 2 map images, establishing their potential as both T 1 and T 2 MRI CAs [151]. Mixed Zn(II)/Gd(III) oxide NPs with approximately 8 mole% of Zn with an average diameter of 2.1 nm were synthesized by Tegafaw et al in their studies.…”
Section: Organic and Inorganic Moleculesmentioning
confidence: 97%
“…In recent years, different groups [31][32][33][34][35] have produced and characterized paramagnetic rare-earth-containing particles, reporting interesting properties for MRI. Gadolinium oxide and hydroxide particles were shown to present rather efficient T 1 relaxation, with relaxivities ranging from 4 to 40 s -1 mM -1 at 1.5 T. On the contrary, dysprosium oxide particles have almost negligible longitudinal relaxivity at all fields, but they could represent an alternative T 2 contrast agent, especially for high magnetic fields, since their transverse relaxivity increases with the field as first shown at high fields by Norek et al [7] and later confirmed at low and intermediate fields and also for gadolinium hydroxide particles [9].…”
Section: Introductionmentioning
confidence: 99%
“…Surfacecoated magnetic nanoparticles have been intensively investigated as MRI contrast agents because they often showed higher water proton relaxivities than molecular chelates. Until now, the iron oxide nanoparticles [7][8][9], the manganese oxide nanoparticles [10][11][12], the gadolinium oxide nanoparticles [13][14][15][16], and the gadolinium compound nanoparticles [17][18][19] have been investigated.…”
Section: Introductionmentioning
confidence: 99%